2014
DOI: 10.14260/jemds/2014/2224
|View full text |Cite
|
Sign up to set email alerts
|

Clinicohematological Study of Hemophilia Patients in Bhopal

Abstract: The X-linked inherited coagulation disorders, hemophilia A (Factor VIII deficiency) and hemophilia B (factor IX deficiency), together with Von Willebrand disease comprise 95 to 97 percent of all the Inherited deficiencies of coagulation factors. (1,2) Replacement of the deficient factor is the mainstay of treatment; it may be "on demand" or "prophylactic" to prevent hemarthrosis in severe deficiency. The prevalence of hemophilia A is 1 in 5000 and that of hemophilia B is 1 in 30,000 (3,4) male live births and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
5
4
0
Order By: Relevance
“…20,21 In present study, in 52% patients bleeding starts spontaneously while in 48% patients bleeding starts following major or minor trauma. Similar results are seen in study done by R K Nigam 14 et al (Spontaneous bleed -57%, traumatic bleed-33%). While in study done by Shamoon 22 et al percentage of spontaneous and traumatic bleeding in patients was 32% and 68% respectively.…”
Section: Type Of Haemophilia Number Of Patients Percentagesupporting
confidence: 91%
See 2 more Smart Citations
“…20,21 In present study, in 52% patients bleeding starts spontaneously while in 48% patients bleeding starts following major or minor trauma. Similar results are seen in study done by R K Nigam 14 et al (Spontaneous bleed -57%, traumatic bleed-33%). While in study done by Shamoon 22 et al percentage of spontaneous and traumatic bleeding in patients was 32% and 68% respectively.…”
Section: Type Of Haemophilia Number Of Patients Percentagesupporting
confidence: 91%
“…Which is corresponding to Saurabh Mishra 15 et al (58%) and MM Uddin 11 et al (60%). Family history was positive in 70% of cases in study done by R. K. Nigam 14 et al and 40% in study done by MA Karim 12 et al In most of the studies family history was positive in 40 -70% of cases. These results are in accordance with other studies.…”
Section: Type Of Haemophilia Number Of Patients Percentagementioning
confidence: 91%
See 1 more Smart Citation
“…The higher mutation rate in hemophilia A than hemophilia B could justify the later finding. The results of the current study showed that the moderate cases were more than the mild and the severe ones.This result is compatible with the results of Al Tonbaryet al, (2010) who indicated that the moderate presentation represents the majority in 17.2% followed by sever presentationin 4.7%,and Nigam et al, 2014 who found that the frequent type of hemophila was moderate group in hemophilia A 87 (38.84%), while our findings differed from these of Al-Beldawi, (2010), andMannuccio (2018), who proved the severe bleeding cases were more than the moderate cases.…”
Section: Discussionsupporting
confidence: 93%
“…These inhibitors can signi icantly increase morbidity status in terms of bleeding complications. Hemarthrosis is the most commonly manifested co-morbidity of hemophilia pathogenesis (Nigam et al, 2014). Severity of Haemophilia A can be diagnosed clinically with lower coagulation factor level of <0.01 IU/ml and < 1% of normal (Uijl et al, 2011).…”
Section: Introductionmentioning
confidence: 99%